2008
DOI: 10.1080/03098260701731496
|View full text |Cite
|
Sign up to set email alerts
|

Experimenting with Active Learning in Geography: Dispelling the Myths that Perpetuate Resistance

Abstract: While some geographers have embraced active learning as a means to engage students in a course, many others stick to conventional teaching methods. They are often deterred by suggestions that it can be difficult to implement active learning where students have no prior knowledge of a subject, that active learning requires too much work of lecturers and students, and that there are significant institutional constraints to implementing active learning. In this article the authors draw on their experiences of uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 14 publications
2
52
0
1
Order By: Relevance
“…The results of the current study are consistent with the results of Scheyvens, et al (2008), which showed that active learning raises students' motivation to learn, as well as Alenzi (2010), which showed that active learning contributes to improving motivation toward learning among outstanding students.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the current study are consistent with the results of Scheyvens, et al (2008), which showed that active learning raises students' motivation to learn, as well as Alenzi (2010), which showed that active learning contributes to improving motivation toward learning among outstanding students.…”
Section: Discussionsupporting
confidence: 82%
“…Tandogan and Orhan (2007) indicated that problem solution based on active learning strategies contributes to improving the academic achievement and acquiring scientific concepts among seventh grade students in science. Scheyvens et al (2008) confirmed that the active learning increases the motivation of students to learn and work to form positive trends, also it increases the students' understanding of school subjects and promotes self-learning and their confidence in their ability to learn, the study also resulted that active learning improves academic achievement. Ravi et al (2009) indicated the importance of active learning for students to acquire the following skills: resource management, organization, personal skills, interpersonal, and communication skills.…”
Section: International Research In Educationsupporting
confidence: 56%
“…Those who support active learning claim that active learning methods could contribute to the development of high level thinking skills in students. And this will encourage a "deeper" approach that forms a basis for students to learn and to make some meaning of the knowledge (Bonwell & Eison, 1991;Gibbs, 1992;Hanson & Moser, 2003;Scheyvens et al, 2008). Bonwell and Eison (1991, p. 19), have listed the various features of active learning:…”
Section: Introductionmentioning
confidence: 99%
“…This approach is generally called "active learning" (Cook & Babon, 2016;Gibbs, 1992). Even if the active learning does not have a universal definition, Scheyvens et al (2008) make the best definition of the active learning by saying what it is not: students passively listen to the speech given by the instructor. Those who support active learning claim that active learning methods could contribute to the development of high level thinking skills in students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation